Parametric analisys of interaction between angular and translational vibrations of vibration-sensitive systems - Shardakov, Igor’ Nikolayevich; Glot, Irina Olegovna; Shestakov, Aleksey Petrovich; Sobyanin, Kirill Valentinovich; Gubskiy, Dmitriy Vital’yevich (Computational Continuum Mechanics, 2019)
Modern radio-TV complexes, electronic equipment and navigation systems placed on moving objects (aircrafts, ships, cars and others) are subjected to pulse and vibrational mechanical loads, which may distort the device characteristics and even destroy them. Therefore, there is a need to minimize unwanted movements of these devices. The effective way to solve this problem is the organization of passive vibration isolation of a device. This article explores the mechanical vibrations of a block of shock-sensitive electronic devices fixed on a rigid platform of a supporting structure. The block is isolated from the external structure using 4 dampers. The platform is subjected to translational vibrations in three mutually orthogonal directions. As a result, angular oscillations occur in the insulated block. Mathematical modeling of the block response to external disturbances is carried out in the framework of the classical theory of rigid body dynamics. A series of numerical experiments was performed to simulate the response of the insulated block to an external periodic action. In the simulation, the stiffness and energy dissipation coefficients of dampers as well as the positions of the center of mass are varied. It is shown that the deviation of the position of the center of mass relative to the center of rigidity, as well as a change in the stiffness and energy dissipation coefficients of dampers within the spread around their mean values causes a significant increase in the angular oscillations of the insulated block.